ANALYSIS OF THE COMMUNICATIVE METHOD OF FOREIGN LANGUAGE TEACHING. - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
Activity modeling is done by modeling its units, so the question of the nature of such units should be considered fully and comprehensively. The unit of activity is usually understood as the minimal segment of that activity that retains its overall structure and semantic features. Representatives of modern linguistics, which can be described as communicative linguistics, think that neither the vocabulary of the language, the grammatical form, nor the phonemic composition form an independent communicative unit.